Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ajgw.12080
|View full text |Cite
|
Sign up to set email alerts
|

Within-vineyard variability in vine vegetative growth, yield, and fruit and wine composition of Cabernet Sauvignon in Hawke's Bay, New Zealand

Abstract: Background and Aims: Spatial and temporal variability of vine vigour within a vineyard block, associated with variation in soil physical and chemical properties, affects yield, and fruit and wine composition. The objectives of this study were to measure this variability and possible causes for a commercially important vineyard area in Hawke's Bay, New Zealand. Methods and Results: Three vigour classes, and measurement of vine nutrient and water status, vegetative growth and canopy attributes, yield, fruit ripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
1
24
0
5
Order By: Relevance
“…Echeverría et al 7 indicated that the available water in the root zone is one of the factors that affect plant growth, yield, bunch rot, and berry composition. Similarly, King et al 8 pointed out that the preferred fruits were found in vines cultivated in shallow soils, in which the available soil water was the major control factor. Well drained soils are required to limit waterlogged vine roots, ultimately forcing deep root penetration to find water during times of seasonal drought stress.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Echeverría et al 7 indicated that the available water in the root zone is one of the factors that affect plant growth, yield, bunch rot, and berry composition. Similarly, King et al 8 pointed out that the preferred fruits were found in vines cultivated in shallow soils, in which the available soil water was the major control factor. Well drained soils are required to limit waterlogged vine roots, ultimately forcing deep root penetration to find water during times of seasonal drought stress.…”
Section: Introductionmentioning
confidence: 93%
“…indicated that the available water in the root zone is one of the factors that affect plant growth, yield, bunch rot, and berry composition. Similarly, King et al . pointed out that the preferred fruits were found in vines cultivated in shallow soils, in which the available soil water was the major control factor.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations